Investigation of mechanical and wear properties of 17–4 PH materials produced with different patterns in atomic diffusion additive manufacturing technology - Ufuk Tasci; Taha Alper Yilmaz (Engineering Science and Technology, an International Journal)
This study investigates the effect of different infill patterns-Solid Fill, Gyroid Fill, and Triangular Fill-on the mechanical and tribological performance of 17–4 PH stainless steel components fabricated using the Atomic Diffusion Additive Manufacturing (ADAM) process on a MetalX™ system. Samples were produced according to the optimized parameters of the ADAM method and evaluated through density measurement, microhardness, tensile testing, transverse rupture strength (TRS), and wear tests. The Solid Fill structure exhibited the highest performance, achieving a relative density of 96.4 %, tensile strength of 948 MPa, and TRS of 1848.5 MPa. Additionally, it showed the lowest wear rate and minimal porosity. Gyroid and Triangular Fill samples offered reduced mechanical properties but presented advantages in material savings. These findings demonstrate that ADAM technology enables the production of high-performance parts with tailored mechanical properties through infill optimization, making it a promising method for advanced manufacturing sectors such as aerospace, automotive, and defense.